Parametric analysis of economical bay dimensions for steel floor framing - Wolf, Aaron (Kansas State University, 2016)
This thesis intends to act as a resource for structural engineers or architects to make informed decisions for selecting economical bay dimensions for a steel‐framed building. This thesis utilizes a parametric study to investigate how different design variables affect economical bay sizes for a typical steel‐framed building. While there are many ways to define an “economical bay”, this analysis defines an economical bay size as the bay size that uses the least steel, measured in pounds per square foot of floor area. Although other factors contribute to the overall economy of a steel bay, this analysis only considers the weight of steel. Investigated parameters include beam spacing, beam span, girder span, floor live load intensity, and composite versus non‐composite construction. Beam center‐to‐center spacing varies from four feet to 12 feet in two‐foot increments. Beam spacing varies independently from beam span. Beam spans range from 20 feet to 52 feet in four foot increments. Girder spans also range from 20 feet to 52 feet in four foot increments. Beam and girder spans vary independently of one another. Floor live loads include 50 lb/ft², 75 lb/ft², and 100 lb/ft². The effect of member construction type is also evaluated in this analysis by considering both composite and non‐composite beams and girders. This analysis finds that 20‐foot by 20‐foot bays use the least steel per square foot, while 52‐foot by 52‐foot bays use the most. Identical bays framed with girders spanning the long direction use less steel than with beams spanning the long direction. Beams contribute the majority of the steel weight in the structure, while columns contribute the least. Live load intensity produces minimal effect on the steel weight, while the use of composite construction saves 30‐40% of steel weight versus non‐composite construction.
Keywords: steel framing